Information exchange under uncertainty: The case of unconventional gas development in the United Kingdom. (September 2017) - Fischer, Manuel; Ingold, Karin; Ivanova, Svetlana
Abstract: New techniques of unconventional oil and gas extraction, such as hydraulic fracturing, challenge current political, institutional and administrative practices in how to regulate activities in the underground. Conflicts of interests between economic promotion, landscape and natural resource protection, and new trends on energy markets are further intensified by the fact that techniques of oil and gas extraction come with a considerable amount of uncertainties regarding ecological and health impacts. Information exchange is one important aspect of how political actors try to reduce uncertainties and conflicts. Based on exponential random graph models (ERGM) for network data, we analyze to what degree ideologies, public authority, existing collaboration and scientific expertise drive information exchange in hydraulic fracturing regulation in the United Kingdom. Results show that technical and political information exchange have to be disentangled, and that the former is driven by expertise and existing collaboration, the latter by ideology, public authority and existing collaboration.